Barriers and Facilitators to Food Policy Development in Fiji. Issue 4 (December 2018) - Latu, Catherine; Moodie, Marj; Coriakula, Jeremaia; Waqa, Gade; Snowdon, Wendy; Bell, Colin
Introduction: Policy interventions can encourage healthier dietary choices and help prevent noncommunicable diseases (NCDs). Consequently, governments are seeking to develop and implement food-related policies, but little research on food-related policies is available to guide policy development. Objective: This study aims to provide an in-depth examination of barriers and facilitators to food-related policy development in Fiji. Method: Case studies were undertaken on 7 food-related policies that were recommended for action in 2010. Data were collected in 2015 through 20 key informant interviews with purposely selected officers from relevant government ministries, consumer advocacy groups, and academia as well through document reviews. The interview data were analyzed thematically. Results: Findings were categorized into major themes: leadership, nature of the policy and political environment, and collaboration within and across sectors. Barriers included leaders not being supportive of progressing policy, the content of the policy influencing its adoption, and a lack of consultation with relevant stakeholders. Facilitators included certain leaders' commitment to driving the policy combined with the support of government at time of deliberation. Good collaboration between government sectors and other stakeholders also facilitated policy endorsement. Conclusion: Attention to leadership, collaboration, policy content, and political environment is likely to enhance the process of developing and implementing food policies targeting NCD prevention in Fiji.